In vivo study of pharmacokinetic parameters of a new combination drug based on citicoline and memantine - Boris B. Sysuev; Damir K. Salakhetdinov (Belgorod National Research University, 2021)
Introduction: Cognitive impairment (dementia) is one of the most common pathologies with increasing numbers of patients. Most often they are the symptoms of Alzheimer's disease and vascular brain diseases, for which such drugs as memantine and citicoline are used. The development of a combination drug with these active pharmaceutical ingredients can significantly increase the effectiveness of therapy. Materials and methods: The pharmacokinetics of memantine and citicoline combination drug was evaluated in comparison with the marketed drugs (reference drugs) of these pharmaceutical substances approved for medical use by determining their content in blood plasma of experimental animals after a single oral administration. Results: Seventy-two hours after the administration of memantine drug, about 5% and 17% of the maximum concentration of memantine released from Akatinol Memantine and the developed combination drug were found in blood plasma, respectively. By the 120th hour after the beginning of the experiment, no memantine was detected in blood plasma of any animal. By the 24th hour after the beginning of the experiment, about 46% and 50% of the maximum concentration of citicoline released from the developed combination drug and the Ceraxon drug were found in blood plasma of the rabbits, respectively. Discussion: It was detected that the amounts of released memantine and citicoline from the developed combination drug exceeded the amounts of the appropriate pharmaceutical substances released from the reference drugs. The bioavailability of these substances from the developed combination drug was higher than from the marketed mono formulations used as reference drugs. Conclusion: Based on the obtained results of memantine and citicoline concentrations in bioassays, the main pharmacokinetic parameters of the studied preparations were calculated, the results of which showed the superiority of the developed combination drug over the reference drugs.